From Corruption to State Capture: Assessing the Relevance of Anti-Corruption Institutions in Ghana - Donpaala, Stephen Delle; Mohammed, Abdul-Rahaman (Research Parks Publishers, 2023)
Over the course of time, corruption has evolved into a pervasive force that consistently undermines the moral fabric of society. It is widely acknowledged as the foremost impediment to a nation's progress, particularly in the realms of poverty alleviation and the reduction of inequality. This is especially true especially for developing countries like Ghana. The insidious and escalating nature of corruption renders it highly contagious across all sectors of society, thereby necessitating a thorough assessment of the phenomenon. Hence, the paper holistically, examined the issue of corruption specifically on the topic “from corruption to state capture, the relevance of anti- corruption institution”. Salient issues that surfaced included an overview of corruption and state capture, some anti-corruption institutions and their role as well as the challenges encountered by these anti-corruption institutions in performing their functions as well astheir role and significance in solving a state capture level of corruption through informal strategies like Co-optation, Control and Camouflage. The paper adopted a qualitative methodology for flexibility and broader data. Out of this a conclusion was drawn and some recommendations made for policy makers attention and action.